Evaluating a filtering and recirculating system to reduce dust drift in simulated sowing of dressed seed and abraded dust particle characteristics. Issue 6 (24th October 2016) - Biocca, Marcello; Pochi, Daniele; Fanigliulo, Roberto; Gallo, Pietro; Pulcini, Patrizio; Marcovecchio, Francesca; Perrino, Cinzia
Abstract: BACKGROUND: The pneumatic precision drills used in maize sowing can release dust owing to abrasion of dressed seed; the drift of dust containing insecticide active ingredients is harmful to honey bees. Therefore, we developed a device for drills that uses partial recirculation and filtration of the air by means of an antipollen and an electrostatic filter. RESULTS: Tests were carried out by simulating the sowing of seed treated with imidacloprid, thiamethoxam, clothianidin and fipronil. Dust released by the drill in different configurations was analysed to assess its mass and active ingredient concentration, size distribution and particle number concentration. In general, particles with a diameter smaller than 2.5 and 10 µm represent about 40 and 75% of the total dust mass respectively. The finest size fraction (<1 µm) contains a higher content of active ingredient. The prototype equipped with both antipollen and electrostatic filters always showed a reduction in dust emission greater than 90% in terms of both total mass and active ingredient amount, with a greater efficiency in the reduction in particles below 4 µm. CONCLUSION: This study presents an engineering solution addressing dust losses during sowing, contributes to the description of abrasion dust fractions and provides suggestions for further development of the prototype. © 2016 Society of Chemical Industry